How is the notion of Latin American social science constructed from Scopus? Convergence between eassay and categorical analysis - Díaz Herrera, Claudio (Revista General de Información y Documentación, 2018)
The purpose of the text is to elucidate the type of writing by which the notion of social sciences is constructed in Latin America once the 21st century has begun. Through an systematic review since the Scopus platform, specific search filters were applied to fulfill the objective. Throwing in first instance 368 publications and after selecting 23 publications according to their thematic relevance in relation to articles that account for the discussion in the theoretical and epistemological construction of the notion of social sciences between 2000 and 2017, it is concluded that both the essay - understood as a theoretical discursive structure of intellectual vocational guidance -, as well as the analysis of categorical variables, are the main resources of writing and analysis, by which we can account for the discussion regarding the notion of social sciences where epistemological discussion and scientometric studies give account of a reflection of the study area.